An estimate of burnout prevalence among oncology nurses - Helaß, Madeleine; Maatouk, Imad (BMC nursing, 2024)
Registered nurses (RNs) in oncology must cope with the suffering of patients, the inevitability of death and their own transience. This poses a possible risk for the development of burnout, which can result in low job satisfaction and ultimately an increased intention to leave the job. Our aim was to assess psychological distress in registered nurses working in oncology.